2020
DOI: 10.3390/ijerph17103543
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Adolescents’ Health Literacy in Europe: Findings from the HBSC Study

Abstract: (1) Background: There is a need for studies on population-level health literacy (HL) to identify the current state of HL within and between countries. We report comparative findings from 10 European countries (Austria, Belgium (Fl), Czechia, England, Estonia, Finland, Germany, Macedonia, Poland, and Slovakia) on adolescents’ HL and its associations with gender, family affluence (FAS), and self-rated health (SRH). (2) Methods: Representative data (N = 14,590; age 15) were drawn from the HBSC (Health Behavior in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
0
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(110 citation statements)
references
References 31 publications
(63 reference statements)
9
67
0
15
Order By: Relevance
“…Measuring and monitoring adolescent health literacy is an integral part of designing and delivering health promotion programs that address health inequities and improve health outcomes 1 . Evidence has shown that there is a social gradient in adolescent health literacy, 23,24 which in turn leads to health promotion outcomes. Adolescents with high health literacy levels are more likely to have health‐promoting behaviours, communicate effectively with health professionals, and perceive their health status as good 4,5,24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measuring and monitoring adolescent health literacy is an integral part of designing and delivering health promotion programs that address health inequities and improve health outcomes 1 . Evidence has shown that there is a social gradient in adolescent health literacy, 23,24 which in turn leads to health promotion outcomes. Adolescents with high health literacy levels are more likely to have health‐promoting behaviours, communicate effectively with health professionals, and perceive their health status as good 4,5,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that there is a social gradient in adolescent health literacy, 23,24 which in turn leads to health promotion outcomes. Adolescents with high health literacy levels are more likely to have health‐promoting behaviours, communicate effectively with health professionals, and perceive their health status as good 4,5,24 . Due to the small sample size, we did not test the reliability and validity of the three health literacy instruments and did not investigate the relationship between adolescent health literacy and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the Demographic and Health Surveys, McClintock et al [ 29 ] found that the prevalence of poor health literacy among respondents aged 15–49 years ranged from 36.1% in Namibia to 91.5% in Niger across 14 sub-Saharan countries. As for children and adolescents, the Health Behaviour in School-aged Children study shows that, in 10 countries (e.g., Austria, England, Finland), a total of 13.3% of participants have low levels of health literacy, ranging from 6.0% to 17.7% across countries [ 30 ].…”
Section: What Is Known Already?mentioning
confidence: 99%
“…The approach of “learning by playing” could be especially essential and effective with young kids. In various literature reviews, a number of approaches were identified and studies performed for youth or secondary school students [ 6 , 8 , 21 , 22 ] Paakkari et al (2020) [ 22 ], for example, compared the level of health literacy of 15-year-old students in 10 European countries (N = 14,590) using the Health Literacy for School-Aged Children (HLSAC) as an instrument. The findings revealed that 13% of the students reported low health literacy, whereas 67% had a moderate level of health literacy, and 20% reached a high level.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly the same proportion of low health literacy was exposed in a representative study by Sukys et al (2019) [ 23 ] among Lithuanian students from the 7th to 10th grades. The highest mean scores in the study of Paakkari et al (2020) were found in Macedonia and Finland [ 22 ]. The Finish result corresponds to the study of Paakkari et al (2017) [ 24 ] with seventh and ninth graders (N = 3833) who demonstrated that 33% of the participants showed a high level of health literacy and 60% had a moderate level of health literacy.…”
Section: Introductionmentioning
confidence: 99%